Analysis of Interdomain Interactions of the Androgen Receptor - Wilson, Elizabeth M. (2011)
High-affinity binding of testosterone or dihydrotestosterone to the androgen receptor (AR) triggers the androgen-dependent AR NH(2)- and carboxyl-terminal (N/C) interaction between the AR NH(2)-terminal FXXLF motif and the activation function 2 (AF2) hydrophobic binding surface in the ligand-binding domain. The functional importance of the AR N/C interaction is supported by naturally occurring loss-of-function AR AF2 mutations where AR retains high-affinity androgen binding but is defective in AR FXXLF motif binding. Ligands with agonist activity in vivo such as testosterone, dihydrotestosterone, and the synthetic anabolic steroids induce the AR N/C interaction and increase AR transcriptional activity in part by slowing the dissociation rate of bound ligand and stabilizing AR against degradation. AR ligand-binding domain competitive antagonists inhibit the agonist-dependent AR N/C interaction. Although the human AR N/C interaction is important for transcriptional activity, it has an inhibitory effect on transcriptional activity from AF2 by competing for p160 coactivator LXXLL motif binding. The primate-specific AR coregulatory protein, melanoma antigen gene protein-A11 (MAGE-A11), modulates the AR N/C interaction through a direct interaction with the AR FXXLF motif. Inhibition of AF2 transcriptional activity by the AR N/C interaction is relieved by AR FXXLF motif binding to the F-box region of MAGE-11. Described here are methods to measure the androgen-dependent AR N/C inter-domain interaction and the influence of transcriptional coregulators.